2001
DOI: 10.1002/chin.200126102
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: A Novel Palladium‐Mediated Coupling Approach to 2,3‐Disubstituted Benzo[b]thiophenes and Its Application to the Synthesis of Tubulin Binding Agents.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Although the synthesis of 2,3-disubstituted benzothiophenes is well documented, to our knowledge, only one report deals with the synthesis of 2-aryl-3-(α-styryl)benzothiophenes through a Wittig reaction . We have recently shown that the electrophilic cyclization of 2-(1-alkynyl)thioanisoles in the presence of N -methylpyrrolidin-2-one hydrotribromide (MPHT) provides a mild, high yielding synthesis of 3-bromo-benzothiophenes .…”
Section: Resultsmentioning
confidence: 99%
“…Although the synthesis of 2,3-disubstituted benzothiophenes is well documented, to our knowledge, only one report deals with the synthesis of 2-aryl-3-(α-styryl)benzothiophenes through a Wittig reaction . We have recently shown that the electrophilic cyclization of 2-(1-alkynyl)thioanisoles in the presence of N -methylpyrrolidin-2-one hydrotribromide (MPHT) provides a mild, high yielding synthesis of 3-bromo-benzothiophenes .…”
Section: Resultsmentioning
confidence: 99%
“…X-ray crystal structure analysis of 10 revealed the A-ring to be rotated toward the D-ring in a pseudo-π-stacking arrangement . It was concluded that this conformation is likely to be important to binding, and early SAR studies within our group indicated that the A- and D-rings of 10 may coincide with the A- and B-rings of 4 . For example, the introduction of a 3′-hydroxyl to the D-ring of 10 (compound 11 ) increased structural analogy to 4 and increased potency (entry 3, Table ). Also, removal of the B-ring in 11 was well tolerated, giving an even more potent compound 14 (entry 4, Table ).…”
Section: Resultsmentioning
confidence: 73%
“… a Inhibition of extent of microtubule assembly was the parameter measured. b All data were obtained from the same laboratory: refs . c The rate but not the extent of tubulin polymerization was inhibited by 50%. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations